Short communication: An overview of the trematodes fauna of pool frog Pelophylax lessonae (Camerano, 1882) in the Volga Basin, Russia: 2. Larval stages - IGOR V CHIKHLYAEV; ALEXANDER B RUCHIN; ALEXANDER I FAYZULIN (Nusantara Bioscience, 2019)
Abstract. Chikhlyaev IV, Ruchin AB, Fayzulin AI. 2019. Short communication: An overview of the trematodes fauna of the pool frog Pelophylax lessonae (Camerano, 1882) in the Volga Basin, Russia: 2. Larval stages. Nusantara Bioscience 11: 106-111. This paper presents data on the trematodes fauna of the pool frog Pelophylax lessonae (Camerano, 1882) from 13 regions of the Volga Basin. It consolidates data from different authors over the past 30 years, supplemented by our own research results. There are authentically known findings of 10 trematodes species at the larval stage of development. The species Codonocephalus urniger (Rudolphi, 1819), mtc., Neodiplostomum spathoides Dubois, 1937, mtc. and Pharyngostomum cordatum (Diesing, 1850), mtc. have been observed for the first time in the given host on the territory of Russia and Volga basin. For each species of trematodes, there is the following information is included: taxonomic position, localization, area of detection, biology, definitive hosts, geographic distribution and degree of host-specificity.